Rancang Bangun Sistem Pembayaran Sekolah Berbasis Web dengan Metode Agile pada SMK Mutiara Bangsa Cengkareng - Resty Wulandari; Dea Nadya Harvie; Putri Salwa Roudonna; Wasis Haryono (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research aims to design and develop a web-based school payment information system using the Agile method at SMK Mutiara Bangsa Cengkareng.The school’s financial management process was still conducted manually using ledgers and spreadsheets, risking data errors and reporting delays.Data collection methods included interviews, observations, and documentation studies.The system was developed iteratively using Agile development cycles, involving stakeholders at each sprint stage.The final result is a web-based application that facilitates payment input, financial reports, transaction history, and role-based access for administrators, staff, teachers, students, and parents.The system improved efficiency, transparency, and accuracy in the school's financial administration.